PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BUKU SAKU PADA MATERI MENULIS HIKAYAT DI KELAS X SMA DARUL ULUM 3 JOMBANG, JAWATIMUR - Hanifa, Nur; Wahyudi, Anton (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
Instructional media development of pocket book pop-up on saga writing material is based on observation and data when collecting information about problem in class. Limited or lack of media type influences toward learning process. Instructional media by using pocket book pop-up can help student in understanding the material because the media used is interesting and the content of the story is easy to understand.There are four focus of this study, are: (1) how is the process  of developing pocket book pop-up instructional media on saga writing material, (2) How is the quality of pocket pop-up instructional media on saga writing material.The research method used in this research is development research by using the Borg and Gall model which consists of ten stages into nine stages consist of (1) the potential and problem stage, (2) the data collection  stage, (3) the product design stage, (4 ) design  validation  stage,(5) design revision  stage, (6) product trial stage, (7) product revision stage,(8) usage trial stage, and (9) product revision stage, (10) mass product stage. The subjects of study in the trial development of  instructional media are class X students of Senior High School Darul Ulum 3 Unggulan Peterongan. The trial is used for data collection in knowing the validity of instructional media.The result of instructional media development of pocket book pop- upin saga writing material on the process of fulfill the validity criteria of validator assessment result is 81 to 95the average value above the KKM. The instructional media developed has the impact of change toward the increase of students’ learning achievement and motivating students when learning in class.